RELATIONSHIP BETWEEN GENDER, STUDY DURATION AND BURNOUT AMONG MEDICAL STUDENTS - Zulfan, Zulfan; Pamungkasari, Eti Poncorini; Maryani, Maryani (Universitas Gadjah Mada, 2023)
Background: Burnout is a psychological syndrome as a response that arises due to chronic interpersonal stressors at work. Burnout in medical students has a negative impact mentally and physically.Aims: This study aims to determine the relationship between gender and study duration with burnout in medical students.Method: This study was conducted using an analytical observational method with a cross-sectional study approach using MBI-SS. The population for this study is composed of medical students at the Faculty of Medicine at Universitas Sebelas Maret, specifically those from the classes of 2019-2021. Samples were selected randomly using a stratified random sampling method. The sample size was 247 students. The data were then analyzed using SPSS 22 for Windows.Result: The results of the analysis showed that there was no significant difference in the level of burnout based on gender with p-value of 0.786, but there was a significant difference in the level of burnout based on the study duration with p-value of 0.044, which the third-year students rank highest in MBI-SS score.Conclusion: The results of this study indicate that there is no significant relationship between gender and burnout levels but there is a significant relationship between study period and burnout levels. These results indicate that the longer the study duration, the higher the burnout level of students.